Cisternal lavage via third ventriculostomy through the fenestrated lamina terminalis after aneurysm clipping: Technical note. (June 2019) - Roelz, Roland; Grauvogel, Jürgen; Scheiwe, Christian; Shah, Mukesch; Beck, Jürgen; Reinacher, Peter C.; Hubbe, Ulrich
Graphical abstract: Highlights: Third ventriculostomy through the lamina terminalis is a simple method to establish a cisternal access. Post-operative cisternal lavage therapy is enabled. DCI may be prevented by cisternal fibrinolysis and spasmolysis. Abstract: Delayed cerebral infarction (DCI) contributes to the burden of morbidity and mortality acquired by patients with aneurysmal subarachnoid hemorrhage (SAH). Cisternal lavage may prevent DCI. Delivery of lavage therapy to the basal cisterns, however, is challenging. Here, we report a novel method for the delivery of cisternal lavage using a cisterno-ventricular catheter (CVC) inserted via the fenestrated lamina terminalis during aneurysm clipping. In two high-risk aSAH patients a CVC was inserted into the third ventricle through the fenestrated lamina terminalis during aneurysm clipping. Post-operatively, continuous cisternal lavage using Urokinase or Nimodipine was applied using an external ventricular drain (EVD) as inflow tract and the CVC as outflow tract. Neurological outcome at 6 months was assessed by modified Rankin scale. Catheter placement into the third ventricle through the fenestrated lamina terminalis was performed without complications. Application of a free-running electrolyte solution containing Urokinase or Nimodipine via the EVD and drainage via the CVC was feasible. Cisternal Nimodipine application normalized sonographic vasospasm in both cases. DCI did not occur. CVC placement for ventriculo-cisternal lavage may represent a useful method for DCI prevention. It can be considered in aSAH patients at risk for DCI if the chiasmatic region is accessed during aneurysm clipping.